2022
DOI: 10.1007/s00402-022-04729-2
|View full text |Cite
|
Sign up to set email alerts
|

Pedobarographic evaluation of five commonly used orthoses for the lower extremity

Abstract: Introduction Orthoses are designed to achieve immobilization or off-loading of certain regions of the foot. Yet, their off-loading capacity for the specific regions has not yet been studied. Therefore, the aim of this study was to analyze the plantar pressure distribution of five commonly applied orthoses for foot and ankle in a healthy population. Materials and Methods Five orthoses (postoperative shoe, forefoot relief shoe, short walker boot, high walker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…However, partial weightbearing can be very challenging or even impossible for elderly people. Casts or walker orthosis may reduce the peak pressure with loading ( 59 ), while early physiotherapy is recommended ( 7 ). Recently, a systematic review found that early permissive weightbearing might not only be safe but even beneficial to elderly people above 80 years for both operatively and conservatively treated unstable ankle fractures ( 60 ).…”
Section: Postoperative Considerationsmentioning
confidence: 99%
“…However, partial weightbearing can be very challenging or even impossible for elderly people. Casts or walker orthosis may reduce the peak pressure with loading ( 59 ), while early physiotherapy is recommended ( 7 ). Recently, a systematic review found that early permissive weightbearing might not only be safe but even beneficial to elderly people above 80 years for both operatively and conservatively treated unstable ankle fractures ( 60 ).…”
Section: Postoperative Considerationsmentioning
confidence: 99%